2018
DOI: 10.3389/fendo.2018.00502
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Hyperhomocysteinemia and Hyperuricemia With Metabolic Syndrome and Renal Function in Chinese Centenarians

Abstract: As the first time worldwide, this study aimed to investigate the relationships of hyperhomocysteinemia and hyperuricemia with metabolic syndrome (MetS) and renal function in Chinese centenarians. The China Hainan Centenarian Cohort Study was performed in 18 cities and counties of the Hainan Province. Home interview, physical examination, and blood analysis were performed on 808 centenarians following standard procedures. All centenarians had a median age of 102 (100–115) years. Prevalence of hyperhomocysteinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…3 Though hyperuricemia in the normal population does not cause clinically obvious symptoms, it is generally considered a precursor of gout and a potential pathogenic factor in metabolic syndrome, hypertension, diabetes, cardiovascular diseases and stroke. 4,5 Therefore, it is important to identify patients who are at high risk of hyperuricemia in a timely manner and treat them, preventing subsequent related diseases and the consequential increased financial burden. Further analysis showed that the prevalence of hyperuricemia gradually increased with increasing age.…”
Section: Introductionmentioning
confidence: 99%
“…3 Though hyperuricemia in the normal population does not cause clinically obvious symptoms, it is generally considered a precursor of gout and a potential pathogenic factor in metabolic syndrome, hypertension, diabetes, cardiovascular diseases and stroke. 4,5 Therefore, it is important to identify patients who are at high risk of hyperuricemia in a timely manner and treat them, preventing subsequent related diseases and the consequential increased financial burden. Further analysis showed that the prevalence of hyperuricemia gradually increased with increasing age.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the nding of the study performed by Chang-Yun Yoon et al, the association was more prominent among male subjects than among female subjects. Notably, previous studies failed to adjust serum uric acid, a well-established confounding factor between obesity and CKD (9,23,24). Compared with the above studies, the number of participants in our study was much larger, thereby allowing careful control of a wide spectrum of potential confounding factors, including serum uric acid, increasing the validity of our results.…”
Section: Discussionmentioning
confidence: 81%
“…Park et al4 observed a significant correlation of serum homocysteine levels with carotid intima-media thickness or renal impairments among hyperuricemic patients. The finding is not surprising based on the previous report that both metabolic syndrome and renal impairments are associated with homocysteinemia 5. Based on their results, the authors proposed a hypothesis where hyperuricemia induces homocysteinemia through renal impairments, which ultimately leads to atherosclerosis 4.…”
mentioning
confidence: 83%